Surgical treatment of cleft lip - Miachon,Mateus Domingues (2014)
We performed a systematic review of the literature on the surgical treatment of cleft lip, emphasizing the prevalence, complications associated with the treatment and the points of disagreement between authors. We conducted a literature cross-sectional search that analyzed publications in books, articles and on the databases SciELO - Scientific Electronic Library Online, PubMed, of the National Center for Biotechnology Information. We conclude that: 1) the severity of the cleft will indicate the technique presenting more advantages; 2) the different approaches indicate that there is no consensus on the optimal technique; and 3) the surgeon experience contributes to choosing the best option.